Moving Beyond Traditional Understandings of Evidence-Based Practice: A Total Evidence and Knowledge Approach (TEKA) to Treatment Evaluation and Clinical Decision Making in Speech-Language Pathology - McCurtin, Arlene; Murphy, Carol-Anne; Roddam, Hazel (Seminars in Speech and Language, 2019)
Evidence-based practice (EBP) is a well-established framework for supporting clinical decision making in the discipline of speech-language pathology. The benefits of using evidence to inform clinical practice are acknowledged by clinicians and researchers alike. Even so, after over two decades of EBP advocacy, much clinical uncertainty remains and models supporting the evaluation of interventions require review and reconsideration. The EBP model, while promoting positive principles, can be argued to be conceptually flawed because it suffers from a lack of attention to and explicit valuing of other forms of knowledge crucial to the formation of realistic and judiciously informed decisions. We propose that the evaluation of interventions would be better supported by an explicit knowledge management approach reflecting a range of evidence and knowledge. One worked example is presented to demonstrate what using such an approach can produce in terms of intervention information.
Keywords: knowledge; evidence; evidence-based practice; intervention evaluation; clinical decision making; critical thinking